2013
DOI: 10.1097/sla.0b013e31826f4969
|View full text |Cite
|
Sign up to set email alerts
|

Adhesiolysis-Related Morbidity in Abdominal Surgery

Abstract: Adhesiolysis and inadvertent bowel injury have a large negative effect on the convalescence after abdominal surgery. The awareness of adhesion-related morbidity during reoperation and the prevention of postsurgical adhesion deserve priority in research and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
176
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(185 citation statements)
references
References 32 publications
4
176
0
5
Order By: Relevance
“…Some asymmetry, however, is due to high incidences derived from high quality studies designed to assess incidences of small bowel obstruction or enterotomy. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] That is, some smaller low quality studies reporting lower incidences were possibly not identified. Our sensitivity analyses, however, showed that our results were quite robust, so we do not expect that these smaller low quality studies would change our results.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Some asymmetry, however, is due to high incidences derived from high quality studies designed to assess incidences of small bowel obstruction or enterotomy. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] That is, some smaller low quality studies reporting lower incidences were possibly not identified. Our sensitivity analyses, however, showed that our results were quite robust, so we do not expect that these smaller low quality studies would change our results.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16] In the SCAR studies, readmissions (defined by identification and diagnostic codes) were used as a proxy for the effect of adhesions. Incidence of adhesions will be difficult to confirm using these diagnostic codes.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 3 more Smart Citations